2018
DOI: 10.1088/1742-6596/1019/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Innovation of flipped learning encouraging better communication and critical thinking skills among accounting students

Abstract: Abstract:Currently the trend among the lecturer to adopt innovation and technology as a tool in the lecture hall in fostering and increasing the positive impact among the students. Innovation and technology may encourage better impact to develop soft skills among the students such as communicate effectively, critical thinking skills, demonstrate appropriate interpersonal skills and teamwork, demonstrate leadership qualities and entrepreneurial skill. Many researchers have attempted to study the efficiency of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The study with a single-group, post-test-only design reported that FC pedagogical approach and model contributed to the encouragement of CT dispositions through interaction, problem-solving strategies and the students' preparation [31]. Other studies using qualitative action research methodology [35] and explorative study [8] also gave the results that students' CT skills have been increased with the implementation of FC.…”
Section: The Influences Of the Applications Of Fc On Developing Ctmentioning
confidence: 98%
“…The study with a single-group, post-test-only design reported that FC pedagogical approach and model contributed to the encouragement of CT dispositions through interaction, problem-solving strategies and the students' preparation [31]. Other studies using qualitative action research methodology [35] and explorative study [8] also gave the results that students' CT skills have been increased with the implementation of FC.…”
Section: The Influences Of the Applications Of Fc On Developing Ctmentioning
confidence: 98%
“…Empirically, many studies have shown that FC is able to facilitate the development of students' CTS in higher education (Andrini, Pratama, & Maduretno, 2019;Chang, Kao, & Hwang, 2020;Chen & Hwang, 2020;Dehghanzadeh & Jafaraghaee, 2018;DeRuisseau, 2016;Huang, 2020;Ibrahim, Khairudin, & Salleh, 2018;Jensen, 2019;Kloppers & Vuuren, 2016;Lee, 2018;Nouri, 2016;Smith et al, 2018;Styers, Van Zandt, & Hayden, 2018). One of the benefits of FC is increasing higher-order thinking skills, including CT (Khlaisang, Teo, & Huang, 2021;Tolbert, 2020), because FC has the potential to create active learning (Smith et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' critical thinking in FC class is found better than in the traditional lecture for nursing students (Dehghanzadeh & Jafaraghaee, 2018) and students of introductory educational psychology (Lee, 2018). FC implementation has improved communication and critical thinking skills in problem-solving for students in accounting (Ibrahim et al, 2018).…”
Section: Introductionmentioning
confidence: 96%